Impact of chronic kidney disease on patients with unprotected left main coronary artery disease treated with coronary artery bypass grafting or drug-eluting stents. Issue 7 (November 2016) - Pan, Yu; Qiu, Qi; Chen, Fang; Li, Xuelian; Yu, Xianpeng; Luo, Yawei; Li, Quan; He, Jiqiang; Gao, Yuechun; Zhang, Xiaoling; Ren, Xuejun
Abstract : Objectives: This study aimed to evaluate clinical outcomes after percutaneous coronary intervention with drug-eluting stents (DESs) or coronary artery bypass grafting (CABG) in unprotected left main coronary artery (ULMCA) disease patients with and without chronic kidney disease. Background: The optimal coronary revascularization strategy for ULMCA disease patients with chronic kidney disease remains uncertain. Methods: The sample included 818 ULMCA disease patients who received DESs ( n =358) or underwent CABG ( n =460). We retrospectively compared clinical parameters and outcomes between different endogenous creatinine clearance rates [estimated glomerular filtration rates (eGFRs), ml/min×1.73 m 2 ]. Results: The incidences of major adverse cardiocerebral events, all-cause death, cardiac death, and stroke were not significantly different between the DES and the CABG groups. The DES group had significantly higher risks of myocardial infarction (MI) and target vessel revascularization than the CABG group. Compared with the CABG group, the hazard ratios for target vessel revascularization were 3.965 [95% confidence interval (CI): 1.743–9.023, P =0.001] in the eGFR of at least 60 group and 46.463 (95% CI: 4.558–473.639, P =0.001) in the eGFR 45–59 group. The rate of MI was higher in patients treated with DESs in the eGFR of less than 45 group (hazard ratio: 14.098, 95% CI: 1.123–176.988, P =0.040). Conclusion: For patients with ULMCA disease at risk of higher repeat revascularization with normal renal function or eGFR of at least 45 ml/min×1.73 m 2, DESs are a safe alternative to CABG. However, for patients with severely reduced kidney function (eGFR<45 ml/min×1.73 m 2 ), DESs should be selected after careful evaluation of MI risk.